2017
DOI: 10.1002/jcp.26142
|View full text |Cite
|
Sign up to set email alerts
|

Novel role for the testis‐enriched HSPA2 protein in regulating epidermal keratinocyte differentiation

Abstract: HSPA2, a poorly characterized member of the HSPA (HSP70) chaperone family, is a testis-enriched protein involved in male germ cell differentiation. Previously, we revealed that HSPA2 is present in human stratified epithelia, including epidermis, however the contribution of this protein to epithelial biology remained unknown. Here, we show for the first time that HSPA2 is expressed in basal epidermal keratinocytes, albeit not in keratinocytes exhibiting features attributed to primitive undifferentiated progenit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 55 publications
1
18
0
Order By: Relevance
“…We found that HBEC cells deficient in HSPA2 protein were less adhesive to fibronectin, laminin, and tenascin but not to collagens (I, II, and IV) or vitronectin ( Figure 4 c). These observations are in line with our previous findings showing that BEAS-2B cells deficient in HSPA2 were less adhesive to fibronectin but not to collagen IV [ 25 ]. Altogether, the results presented in Figure 4 allow us to conclude that HSPA2 in HBEC can play a role in modulating extracellular matrix (ECM) adhesiveness, but not motility.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…We found that HBEC cells deficient in HSPA2 protein were less adhesive to fibronectin, laminin, and tenascin but not to collagens (I, II, and IV) or vitronectin ( Figure 4 c). These observations are in line with our previous findings showing that BEAS-2B cells deficient in HSPA2 were less adhesive to fibronectin but not to collagen IV [ 25 ]. Altogether, the results presented in Figure 4 allow us to conclude that HSPA2 in HBEC can play a role in modulating extracellular matrix (ECM) adhesiveness, but not motility.…”
Section: Resultssupporting
confidence: 93%
“…Previously, we found that human HSPA2 is highly expressed in basal cells in various multilayered epithelia and in bronchial epithelium, which is a type of pseudostratified epithelium [ 21 ]. So far, the understanding of HSPA2 significance in normal somatic cells is limited to epidermal keratinocytes [ 25 ]. It is noteworthy that epidermal keratinocytes [ 25 ] and BEAS-2B cells (this paper) showed similar phenotypic changes after HSPA2 knockdown.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations